CF Patients’ Airway Epithelium and Sex Contribute to Biosynthesis Defects of Pro-Resolving Lipids - Shum, Mickael; London, Charlie M.; Briottet, Maelle; Sy, Khadeeja Adam; Baillif, Vincent; Philippe, Reginald; Zare, Abdolhossein; Ghorbani-Dalini, Sadegh; Remus, Natacha; Tarze, Agathe; Escabasse, Virginie; Epaud, Ralph; et al. (Frontiers in Immunology, 2022)
Specialized pro-resolving lipid mediators (SPMs) as lipoxins (LX), resolvins (Rv), protectins (PD) and maresins promote the resolution of inflammation. We and others previously reported reduced levels of LXA4 in bronchoalveolar lavages from cystic fibrosis (CF) patients. Here, we investigated the role of CF airway epithelium in SPMs biosynthesis, and we evaluated its sex specificity. Human nasal epithelial cells (hNEC) were obtained from women and men with or without CF. Lipids were quantified by mass spectrometry in the culture medium of hNEC grown at air-liquid interface and the expression level and localization of the main enzymes of SPMs biosynthesis were assessed. The 5-HETE, LXA4, LXB4, RvD2, RvD5, PD1 and RvE3 levels were significantly lower in samples derived from CF patients compared with non-CF subjects. Within CF samples, the 12-HETE, 15-HETE, RvD3, RvD4, 17-HODHE and PD1 were significantly lower in samples derived from females. While the mean expression levels of 15-LO, 5-LO and 12-LO do not significantly differ either between CF and non-CF or between female and male samples, the SPMs content correlates with the level of expression of several enzymes involved in SPMs metabolism. In addition, the 5-LO localization significantly differed from cytoplasmic in non-CF to nucleic (or nuclear envelope) in CF hNEC. Our studies provided evidence for lower abilities of airway epithelial cells derived from CF patients and more markedly, females to produce SPMs. These data are consistent with a contribution of CF airway epithelium in the abnormal resolution of inflammation and with worse pulmonary outcomes in women.